Implication of Alkane Carbon and Hydrogen Isotopes for Genesis and Accumulation of Over-Mature Shale Gas: A Case Study of Longmaxi Formation Shale Gas in Upper Yangtze Area - Chen, Zhipeng; Liao, Yun; Liu, Li; Chen, Lei; Wang, Pengtao; Zuo, Yinhui; Ren, Zhanli; Jia, Lianqi; Dang, Wei (Frontiers in Earth Science, 2022)
To clarify the implication of alkane carbon and hydrogen isotopes for the genesis and accumulation of over-mature shale gas, we carried out a comparative study on Longmaxi shale gases from eight blocks in the Upper Yangtze area. The results show that the δ13CCH4, δ13CC2H6, and δ13CC3H8 of Longmaxi shale gas are all positively correlated with Ro. According to the distribution model of δ13C with thermal maturity, the Longmaxi shale gas lies in the reversal stage. Shale gas is a mixture of the kerogen cracking gas and secondary cracking gas, and the mixing ratio of the two cracking gas can be estimated by isotopic fractionation experiments of thermogenic gas. The proportion of secondary cracking gas in the shale gas of the Longmaxi Formation ranges from 33 to 72%. The increase of secondary cracking gas with lower δ13C would reduce the carbon isotope of the shale gas. The δ13CC2H6 and δ13CC3H8 have acute sensitivity to the occurrence of secondary cracking gas, hence they can be used as potential indicators of shale gas content. The decline of gas generation capacity, the reduction of micropores, and the destruction of tectonic movement are the considerable factors leading to the decrease of gas content in high-maturity shale.